2018
DOI: 10.1111/idj.12363
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoints of dentists on the use of bisphosphonates in rheumatology patients

Abstract: Dentists feel ill at ease providing dental surgery to patients receiving BPs. Closer collaboration and better information-sharing between rheumatologists and dentists is necessary to facilitate the administration of BPs in rheumatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Regarding the knowledge of MRONJ among DDS, it was found that younger dentists and recent graduates mastered the subject better (Daron et al, 2018;Patil et al, 2020;Escobedo et al, 2018;Ozkan et al, 2021;Arnaud et al, 2022;Bruckmoser et al, 2021). Moreover, DDS register the medications used by their patients, however, most do not ask the reason why they are being used (Daron et al, 2018;Han, 2021). When it comes to the indications and adverse effects of BP, few professionals knew how to correctly answer the therapeutic indications of antiresorptive and antiangiogenic medications, their trade names, and side effects associated with the oral cavity (Patil et al, 2020;Arnaud et al, 2022;Miranda-Silva et al, 2020).…”
Section: Dds Knowledge On Mronjmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the knowledge of MRONJ among DDS, it was found that younger dentists and recent graduates mastered the subject better (Daron et al, 2018;Patil et al, 2020;Escobedo et al, 2018;Ozkan et al, 2021;Arnaud et al, 2022;Bruckmoser et al, 2021). Moreover, DDS register the medications used by their patients, however, most do not ask the reason why they are being used (Daron et al, 2018;Han, 2021). When it comes to the indications and adverse effects of BP, few professionals knew how to correctly answer the therapeutic indications of antiresorptive and antiangiogenic medications, their trade names, and side effects associated with the oral cavity (Patil et al, 2020;Arnaud et al, 2022;Miranda-Silva et al, 2020).…”
Section: Dds Knowledge On Mronjmentioning
confidence: 99%
“…Regarding the knowledge of MRONJ among DDS, it was found that younger dentists and recent graduates mastered the subject better (Daron et al, 2018;Patil et al, 2020;Escobedo et al, 2018;Ozkan et al, 2021;Arnaud et al, 2022;Bruckmoser et al, 2021). Moreover, DDS register the medications used by their patients, however, most do not ask the reason why they are being used (Daron et al, 2018;Han, 2021).…”
Section: Dds Knowledge On Mronjmentioning
confidence: 99%
See 3 more Smart Citations

Medication-related osteonecrosis: Literature review

Idrovo Campoverde María Coralía,
Bacuilima Ñauta Erika Susana,
Pesántez Alvarado Juan Martín
et al. 2023
World J. Adv. Res. Rev.